Interactive Multimedia Design To Recognize Properties Of Objects Using The ADDIE Method - Desak Made Dwi Utami Putra; Aniek Suryanti Kusuma; Ayu Gede Willdahlia; Ni Kadek Nita Noviani Pande; Ika Amellia Rizanty (Institute of Computer Science (IOCS), 2022)
Natural Sciences is a compulsory subject at SDN 24 Dauh Puri which is theoretical subject, but teachers are required to provide real examples to easily understand. While material properties of objects are difficult to practice, and teachers only provide explanations without examples. This causes students become less understanding and bored with the material properties of objects. So we need to design an interactive multimedia using ADDIE method that serves to visualize the material properties of objects with examples so that students can understand more easily. The results of the system test questionnaire showed that 90.63% of students liked this learning media, 91.64% of students liked the pictures on this learning media, 91.13% of students liked the color in this learning media, 82.53% of students said they could use the media. In this learning, 96% of students know the nature of air, 100% of students know what objects are soluble in water, 97% of students know how the shape changes due to the combustion process, 100% of students know what materials are not easily broken, 100% of students know the nature of the material. of wood, and 87% of students know the raw materials for making paper.